Trade linkages and output multiplier effects a structural VAR approach with a focus on Asia - Abeysinghe, Tilak; Forbes, Kristin (NBER working paper series, 2001)
This paper develops a structural VAR model to measure how a shock to one country can affect the GDP of other countries. It uses trade linkages to estimate the multiplier effects of a shock as it is transmitted through other countries' output fluctuations. The paper introduces a new specification strategy that significantly reduces the number of unknowns and allows cross-country relationships to vary over time. Then it uses this model to examine the impact of shocks to 11 Asian countries, the U.S. and the rest of the OECD. The model produces reasonably good short-term forecasts. Impulse-response matrices suggest that these multiplier effects are large and significant and can transmit shocks in very different patterns than predicted from a bilateral-trade matrix. For example, due to these output-multiplier effects, a shock to one country can have a large impact on countries that are relatively minor bilateral trading partners.